Multicentre observational study on practice of ventilation in brain injured patients: the VENTIBRAIN study protocol - Raimund Helbok; Karim Asehnoune; Giuseppe Citerio; Geert Meyfroidt; Nino Stocchetti; Chiara Robba; Alessia Vargiolu; Jordi Mancebo; Christian Putensen; Rafael Badenes; John Laffey; Robert Stevens; et al. (BMJ Open)
Introduction Mechanical ventilatory is a crucial element of acute brain injured patients’ management. The ventilatory goals to ensure lung protection during acute respiratory failure may not be adequate in case of concomitant brain injury. Therefore, there are limited data from which physicians can draw conclusions regarding optimal ventilator management in this setting.Methods and analysis This is an international multicentre prospective observational cohort study. The aim of the ‘multicentre observational study on practice of ventilation in brain injured patients’—the VENTIBRAIN study—is to describe the current practice of ventilator settings and mechanical ventilation in acute brain injured patients. Secondary objectives include the description of ventilator settings among different countries, and their association with outcomes. Inclusion criteria will be adult patients admitted to the intensive care unit (ICU) with a diagnosis of traumatic brain injury or cerebrovascular diseases (intracranial haemorrhage, subarachnoid haemorrhage, ischaemic stroke), requiring intubation and mechanical ventilation and admission to the ICU. Exclusion criteria will be the following: patients aged <18 years; pregnant patients; patients not intubated or not mechanically ventilated or receiving only non-invasive ventilation. Data related to clinical examination, neuromonitoring if available, ventilator settings and arterial blood gases will be recorded at admission and daily for the first 7 days and then at day 10 and 14. The Glasgow Outcome Scale Extended on mortality and neurological outcome will be collected at discharge from ICU, hospital and at 6 months follow-up.Ethics and dissemination The study has been approved by the Ethic committee of Brianza at the Azienda Socio Sanitaria Territoriale-Monza. Data will be disseminated to the scientific community by abstracts submitted to the European Society of Intensive Care Medicine annual conference and by original articles submitted to peer-reviewed journals.Trial registration number NCT04459884.